2009
DOI: 10.1590/s1414-32832009000100022
|View full text |Cite
|
Sign up to set email alerts
|

"Ligar gente, lançar sentido: onda branda da guerra" a propósito da invenção da residência multiprofissional em saúde

Abstract: Encontro-me, mais uma vez, com o texto de Daniela Dallegrave, acompanhada pela professora Maria Henriqueta Luce Kruse, relativo à invenção da residência multiprofissional em saúde (RMS). Nos encontros anteriores, Daniela formulava um argumento à pesquisa ou interpretava a exploração de campo desse argumento: o que teria motivado as manifestações, provenientes da categoria médica, de vigoroso combate à RMS como modalidade de formação especializada na área? Não era o conjunto do debate sobre a residência (como m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…Ademais, o uso de medicamentos para dormir teve, preocupantemente, uma alta pontuação nesta pesquisa, sendo que esse elevado score pode estar relacionado à exaustão emocional e a despersonalização, devido à influência da alta carga horária de trabalho (60 horas semanais), podendo ao logo da residência causar o acúmulo de sobrecarga física e emocional Research, Society and Development, v. 9, n. 9, e44910910976, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i19.10976 (Asaiag, et al, 2010;Moreira et al, 2016). Outra questão importante e que merece ser investigada mais profundamente, está relacionada aos indivíduos que fazem uso de medicamentos para dormir, os quais apresentam características de transtornos primárias do sono, tais como, sonolência e dificuldade para despertar do sono, que afetam o ciclo vigília-sono, conforme afirma (Orlandi & Noto, 2005;Ceccim, 2009;Silva et al, 2015).…”
Section: Discussionunclassified
“…Ademais, o uso de medicamentos para dormir teve, preocupantemente, uma alta pontuação nesta pesquisa, sendo que esse elevado score pode estar relacionado à exaustão emocional e a despersonalização, devido à influência da alta carga horária de trabalho (60 horas semanais), podendo ao logo da residência causar o acúmulo de sobrecarga física e emocional Research, Society and Development, v. 9, n. 9, e44910910976, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i19.10976 (Asaiag, et al, 2010;Moreira et al, 2016). Outra questão importante e que merece ser investigada mais profundamente, está relacionada aos indivíduos que fazem uso de medicamentos para dormir, os quais apresentam características de transtornos primárias do sono, tais como, sonolência e dificuldade para despertar do sono, que afetam o ciclo vigília-sono, conforme afirma (Orlandi & Noto, 2005;Ceccim, 2009;Silva et al, 2015).…”
Section: Discussionunclassified
“…It should be observed that the notion of meeting in this case is micropolitical, in which the participants in the meeting are always willing to contribute under intercessor alterities. 17 The meetings are pedagogical and operate against homogenizing practices, with exchanges between the participants' knowledge domains and practices, thus constructing a universe of educative processes in action, in a continuous and intense flow of convocations, de-territorializations and inventions. 18 Based on this encounter, interdependence and interaction exists among the actors for the production of health, with a view to constituting a new collective subject, in view of the creation of a space of "inter" relations, in which the residents can daily invent their autonomy and the production of health acts in an intersubjective relationship.…”
Section: What Could Be Perceived In This Residency Is That It Is Purementioning
confidence: 99%
“…As in care procedures, there are a myriad of diagnostic possibilities that circumvent the experience of illness even before the supposed diseased bodies present themselves to the objectification of a professional look. Disease subscribed to a powerful regime of established truth, "represented by the voice of the medical-hegemonic knowledge-power-desire" 8 , makes health the maximum value to be achieved at the price of its extirpation.…”
Section: Transvaluation Of Valuesmentioning
confidence: 99%